Cardiac Immobilization in Beating Heart Surgery Using Pericardial Bands - Sirivella, Srikrishna; Gielchinsky, Isaac (Scientific Research, 2012)
A novel technique of stabilization of the coronary targets with autogenous pericardial bands is described in off pump coronary revascularizations. Pericardial bands are placed across the coronary targets and snared to the pericardial well for local cardiac immobilization. This technique can be used as an alternate to mechanical stabilizers for immobilization of the coronary targets.
Keywords: Coronary Bypass Surgery; Cardiac; Off Pump CABG